Nadolol plus isosorbide mononitrate alone or associated with band ligation in the prevention of recurrent bleeding: a multicentre randomised controlled trial. Issue 8 (12th February 2009) - García-Pagán, J C; Villanueva, C; Albillos, A; Bañares, R; Morillas, R; Abraldes, J G; Bosch, J; ,
Abstract : Background and aims: Previous clinical trials suggest that adding non-selective beta-blockers improves the efficacy of endoscopic band ligation (EBL) in the prevention of recurrent bleeding, but no study has evaluated whether EBL improves the efficacy of beta-blockers + isosorbide-5-mononitrate. The present study was aimed at evaluating this issue in a multicentre randomised controlled trial (RCT) and to correlate changes in hepatic venous pressure gradient (HVPG) during treatment with clinical outcomes Methods: 158 patients with cirrhosis, admitted because of variceal bleeding, were randomised to receive nadolol+isosorbide-5-mononitrate alone (Drug: n = 78) or combined with EBL (Drug+EBL; n = 80). HVPG measurements were performed at randomisation and after 4–6 weeks on medical therapy. Results: Median follow-up was 15 months. One-year probability of recurrent bleeding was similar in both groups (33% vs 26%: p = 0.3). There were no significant differences in survival or need of rescue shunts. Overall adverse events or those requiring hospital admission were significantly more frequent in the Drug+EBL group. Recurrent bleeding was significantly more frequent in HVPG non-responders than in responders (HVPG reduction ⩾20% or ⩽12 mm Hg). Among non-responders recurrent bleeding was similar in patients treated with Drugs or Drugs+EBL. Conclusions: Adding EBL to pharmacological treatment did not reduce recurrent bleeding, the need for rescue therapy, or mortality, and was associated with more adverse events. Furthermore, associating EBL to drug therapy did not reduce the high rebleeding risk of HVPG non-responders. ISRCTN26221020